Nutritional support in critical patients in the Intensive Care Unit. - Gutiérrez-Plaza , J.P.; 1 Barbosa-Rivas, F.A.; Guzmán-, Daniel H.; Cárdenas-Cortés , A.M.; Niño-Castañeda , M. S.,3; Moran-Martínez , J.; Betancourt-Martínez , N.D.; Esquivel-Franco, C.G.* (Revista de Ciencias Médicas Torreón, 2026)
Nutritional support (NS) refers to the provision of nutrients enterally or parenterally with the purpose of maintaining an adequate nutritional status in critically ill patients in whom normal nutrition is not possible. The patient who is admitted to the Intensive Care Unit (ICU) presents an alteration in a vital organ and various metabolic disorders that lead to requiring more energy and protein, deterioration of the immune system, body composition and gastrointestinal function. Nutritional support is administered to patients by nursing staff. A systematic review was carried out with the methodology of Holly Salmond and Saimbert, the eligibility criteria were applied, which were with the PIO question (Problem, Intervention and Results). With a bibliographic search analysis period it was during the year 2022. The PRISMA methodology was applied. This study identifies that the nutritional support of patients in critical condition is very important for the favorable evolution of their health status, starting early as an added treatment. To date, there is no general caloric contribution for patients in critical condition. serious since very important parameters such as the pathology and the general state of health of the patient have to be evaluated; However, the route of administration is one of the variables since both require specific nursing care in administration.